CRITICAL TASTE REFERENCES IN THE BOOK (BE AS VAST AS AIR) BY THE CRITIC HATEM SAKR (World Bulletin of Social Sciences, 2022)
This study sought to reveal the sources and references to the critical taste of Dr. Hatem Sakr through his book Be as vast as the air - in which he dealt with the notebooks of the plastic artist Ghassan Ghayeb - and the reason behind dealing with these notebooks is that they depart from the systemic and traditionalism that many artists followed, in addition to that, he mainly works on The recipient has a space in completing the aesthetic and semantic image of the text. In this study, Al-Sakr’s effort is focused on discovering Ghassan’s absent references and his relationships with poetic texts. It is done with craftsmanship and creative craftsmanship in which the reference is hidden once, and half of it is shown once, and sometimes the reference is a semantic image that departs from the connotations carried by the texts before entering it in the books of Ghassan Absent, which has become bearing a new semantic dimension